Enhancing Health Literacy and Family Competency in Post-Stroke Care Through Health Education: A Community-Based Intervention - Rahmania Ambarika; Novita Ana Anggraini; Herman Adhi Wijayanto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The lack of knowledge and skills among family members in caring for post-stroke patients can prolong the recovery time and increase the risk of complications. Health education is essential to enhance understanding and optimize caregiver skills. This study examines the effect of structured health education on the knowledge and caregiving skills of families caring for post-stroke patients at the Poncokusumo Community Health Center, Malang. Methodology: This research employed a pre-experimental design with a total population of 35 families with the post stroke patients at Poncokusumo Community Health Center , from which 32 participants were selected using purposive sampling. The research instrument consisted of a questionnaire, and data were analyzed using the Wilcoxon test. Results: The results show that before the health education intervention, half of the participants had a moderate level of knowledge (16 people, 50.0%). After the intervention, nearly all participants demonstrated good knowledge (28 people, 87.5%). In terms of skills, before the intervention, the majority of participants had poor caregiving skills (19 people, 59.4%). After the intervention, most participants improved to a moderate skill level (19 people, 59.4%). There was a significant effect of health education on family knowledge regarding post-stroke care at Poncokusumo Community Health Center, with a p-value of 0.000 (<0.05). Conclusion: Health education is effective in improving family knowledge and skills in caring for post-stroke patients. With structured education, families understand how to care for patients, from mobilization and complication prevention to psychosocial support. Direct training and educational media help them apply skills with more confidence. This increased understanding contributes to better quality of care, accelerates patient recovery, and reduces the risk of complications.